A potential link between the C5a receptor 1 and the β1-adrenoreceptor in the mouse heart - Kuan, Hua Khor; Moore, Tyson A.; Shiels, Ian A.; Greer, Ristan M.; Arumugam, Thiruma V.; Mills, Paul C. (Public Library of Science, 2016)
Purpose: Inflammation may contribute to the pathogenesis of specific cardiovascular diseases, but it is uncertain if mediators released during the inflammatory process will affect the continued efficacy of drugs used to treat clinical signs of the cardiac disease. We investigated the role of the complement 5a receptor 1 (C5aR1/CD88) in the cardiac response to inflammation or atenolol, and the effect of C5aR1 deletion in control of baseline heart rate in an anesthetized mouse model.